Femoral vein thrombosis and total hip replacement. Issue 6081 (23rd July 1977) - Stamatakis, J D; Kakkar, V V; Sagar, S; Lawrence, D; Nairn, D; Bentley, P G
Abstract : Of 160 patients who underwent total hip replacement, 81 developed venographic evidence of thrombi in the operated leg. In 46 cases (57%) the thrombus originated from the femoral vein, and in 43 of these the exact site of origin was defined by venography. In 34 cases (74%) the thrombus arose from the wall of the femoral vein at the level of the lesser trochanter. This region was studied by intraoperative venography in eight patients undergoing total hip replacement, and in every case severe distortion of the common femoral vein was observed, producing almost total occlusion. We suggest that intraoperative damage to the femoral vein results from manipulation of the leg, and that this is one reason why the operation is followed by a high incidence of deep vein thrombosis in the upper femoral region.